3 < x < 4
-4 < x < -3
-2 < x < -1
-3 < x < 0
Correct answer is B
x+13 > 1X+3 = x+13 > x+3X+3
= (x + 1)(x + 3)2 > 3(x + 3) = (x + 1)[x2 + 6x + 9] > 3(x + 3)
x3 + 7x2 + 15x + 9 > 3x + 9 = x3 + 7x2 + 12x > 0
= x(x + 3)9x + 4) > 0
Case 1 (+, +, +) = x > 0 , x + 3 > 0, x + 4 > 0
= x > -4 (solution only)
Case 2 (+, -, -) = x > 0, x + 4 < 0
= x > 0, x < -3, x < -4 = x < -3(solution only)
Case 3 (-, +, -) = x < 0, x > -3, x < -4 = x < -0, -4 < x < 3(solutions)
Case 4 (-, -, +) = x < 0, x + 3 < 0, x + 4 > 0
= x < 0, x < -5, x > -4 = x < -0, -4 < x < -3(solution)
combining the solutions -4 < x < -3
If tan θ = 4/3, calculate sin2 θ - cos2 θ. ...
In triangle XYZ, ∠XYZ = 15o, ∠XZY = 45o and lXYl = 7 cm. Find lYZl....
The sum of 378 and 113 is less than the difference between 18...
Add 54 eight and 67eight giving your answers in base eight...
Consider the statements: p: Stephen is intelligent q: Stephen is good at Mathematics If p&r...